Expectations for endoscopic training during gynaecological specialty training: results of a Germany-wide survey = Erwartungen an die endoskopische Ausbildung während der gynäkologischen Weiterbildung : Ergebnisse einer deutschlandweiten Umfrage - Gabriel, Lena; Schott, Sarah (Geburtshilfe und Frauenheilkunde, 2016)
Question: Endoscopy is an integral part of surgical gynaecology and is playing an increasingly important role in ensuring adequate gynaecological training in the context of specialty training in general. At present, little is known about the expectations and notions of young junior doctors with respect to endoscopic training. For this reason, junior doctors throughout Germany were surveyed on this topic and asked to share their opinions. Methods: Using an anonymized standardized survey, the following information was elicited: importance of endoscopic training, willingness to take courses, expectations for instructors and the hospital, ideas about the number of required operations, both as a surgical assistant and as a surgeon, as well as satisfaction with the current status of training. The questionnaires were sent via the Young Forum (Junges Forum) of the German Society of Gynaecology and Obstetrics (DGGG) and the newsletter of the Working Group for Gynaecological Endoscopy (AGE). Results: The evaluation of the study was based on 109 completed questionnaires. The resident junior doctors were 31 years old on average and were in their third to fourth year of their specialty training on average. The majority of the participants (87 %) considered the learning of endoscopic techniques to be very important and advocated regular participation in endoscopy training courses. Among the participants, 48 % were prepared to invest up to €1500 of their own funds to attend courses up to twice a year during the entire specialty training period. The expectations of the instructors and institutions focused on technical expertise, the willingness and time for teaching and on the number and range of surgical procedures, followed by being granted leave for the courses and having costs covered for the courses. Thirty-eight per cent stated that their expectations had been completely or mostly met and 62 % said they had been met in part or inadequately. Eighty-three per cent of the respondents reported that they would change specialty training institutions in order to achieve their own goals in the context of specialty training. Conclusions: This study presents data for the first time on the satisfaction of young junior doctors and their expectations for endoscopic specialty training. The residents exhibited a high level of interest in endoscopy and a high level of willingness to actively shape the specialty training, including course participation. However, there appears to be a great deal of room for improvement for endoscopic specialty training, independent of the current training institution, training year or sex of the junior doctors.